A planning of templer forest park and templer forest reserve through management plan / Mohammad Zharif Hakimi Mohammad Mazani ... [et al.] - Mohammad Mazani, Mohammad Zharif Hakimi; Mohd Salleh, Nurul Atikah; Sahak, Muhammad Hafiy Safwan; Che Ahamed, Nurul Nabila; Valerian, Teeny; Ishak, Mohamad Fathi Radhi; Mohd Hashim, Nor Hanisah; Chek Sulaiman, Firdaus (2021)
The first step in the management preparation process is identifying specific organizational goals. The planning section should provide a detailed overview of each target, as well as the reasoning behind its selection and the expected outcome of goal-related projects. The goal of this research is to develop a management strategy and thus is involved planning and developing of Templer Forest Eco Park and Templer Forest Reserve strategically. Data collection is via observations, interviews and questionnaire surveys. Through observations, data inventory of natural and physical resources in Templer Forest Eco Park and Templer Forest Reserve were gathered. For natural resources data inventory, flora and fauna of the area is documented as well as the physical resources such as the condition and types of soil, river water quality, infrastructures and amenities located at the vicinity. The identification of issues, concerns and opportunities (ICO) is one of the most important stages in the development of a management plan. Three factors that be considered in Issues, Concerns and Opportunities (ICO): managerial, social, and resources. All of the elements identified during the ICO study will form a list of all of the issues or problems that exist at Templer Forest Eco Park and Templer Forest Reserve. The Recreation Opportunity Spectrum (ROS) and Limited Acceptance Change (LAC) allow for limited growth in the natural environment without endangering or disrupting the park's natural elements. In Recreation Opportunity Spectrum, the study defined the framework for identifying the types of outdoor recreation activities and experiences that the public might desire. Templer Forest Eco Park and Templer Forest Reserve should be preserved as it is valuable to us and the natural habitats. The actions of the park management in order to find a solution to the issues raised in the issues, concerns, and opportunities identifying requirements improved, and some alternatives to those issues are proposed.